‘Mind the gap’ - mapping services for young people with ADHD transitioning from child to adult mental health services - Hall, Charlotte L.; Newell, Karen; Taylor, John; Sayal, Kapil; Swift, Katie D.; Hollis, Chris (BioMed Central, 2013)
Background: Once considered to be a disorder restricted to childhood, Attention Deficit/Hyperactivity Disorder (ADHD) is now recognised to persist into adult life. However, service provision for adults with ADHD is limited. Additionally, there is little guidance or research on how best to transition young people with ADHD from child to adult services.